Special Educational Needs and Disability: The Basics - Wearmouth, Janice; Taylor and Francis (Boca Raton, FL : Routledge, 2018)
Special Educational Needs and Disability: The Basics provides an engaging and comprehensive overview of special educational, and additional support, needs in education contexts in the UK. The third edition of this bestselling publication covers the historical development of special provision and national policy-making, and summarises current and proposed legislation and statutory guidance across England, Scotland, Northern Ireland and Wales, examining the fundamental principles of the field from policy to practice. Additional focus is given to recent legislation in England extending the age range of young people identified as experiencing difficulties from birth to 25 years, and the implications this has for practice. Fully updated to incorporate recent research evidence, this indispensable book covers essential features of policy and practice that teachers need to consider in and outside of the classroom, including: the identification and assessment of young people s special or additional learning and behaviour needs, and/or disabilities approaches to planning in order to meet special or additional learning needs of children and young people ways to address barriers to learning and behaviour associated with a variety of difficulties statutory guidance outlined in the Codes of Practice in England (DfE, 2015), Scotland (2010), Wales (2004) and Northern Ireland (1998) special educational, or additional support, needs provision and the wider children s workforce implications of disability legislation across the UK This is an ideal starting point for all those with questions about what constitutes special educational, or additional support, needs and disability and how to support those children and young people who experience such needs. It is essential reading for trainee and practising teachers, policy-makers and all those working with young people and their families.
Introduction. Frames of reference: special or additional educational needs and disability, learning and behaviour -- Chapter 1 Models of human learning. Behaviourist, constructivist and eco-systemic approaches -- Chapter 2 Special educational, or additional support, needs and disability. Evolution of the field -- Chapter 3 Understanding and addressing difficulties in communication and interaction -- Chapter 4 Understanding and addressing difficulties in cognition and learning -- Chapter 5 Understanding and addressing difficulties in social, emotional and mental health -- Chapter 6 Understanding and addressing sensory and/or physical difficulties and needs -- Chapter 7 Assessment and planning for learners with special educational, or additional support, needs -- Chapter 8 The wider childrens workforce associated with special educational needs provision
Includes bibliographical references and index.
Also available in print format.
Keywords: Special education -- Great Britain; Special education -- Law and legislation -- Great Britain; Children with disabilities -- Education -- Great Britain; Mainstreaming in education -- Great Britain; Children with disabilities -- Education; Mainstreaming in education; Special education; Special education -- Law and legislation; EDUCATION / General; EDUCATION / Teaching Methods & Materials / General; BA Education; Behavioural Difficulties; Classroom Practice; Dyslexia; Dyspraxia; Inclusion; Inclusive Education; Introduction to Special Educational Needs; Janice Wearmouth; Learning Difficulties; National Award for Special Educational Needs Coordination; PGCE; Primary Education; SEN; SENCO; Secondary Education; Special Educational Needs; Special Educational Needs Coordinator; Electronic books